Wait : a novel - Burnham, Gabriella (One World, 2024)
"Elise is out dancing the night before her graduation from college, hundreds of miles from home, when her younger sister Sophie calls to tell her that their mother has gone missing. They soon discover that she was arrested on her way home from work and deported to São Paulo, Brazil. Elise decides to return to her childhood home, Nantucket Island, for the first time in nearly three years to be with her sister and figure out how to bring their mother home. Desperate for an affordable place to live, Elise learns that her best friend from college, Sheba -- a gregarious socialite and heir to the Play-Doh fortune -- has inherited her grandfather's summer mansion on-island. Sheba offers for Elise and Sophie to move into the mansion's guest house. Elise meanwhile secures the same job she had in high school, monitoring a species of endangered birds that have laid eggs on a remote beach. But she finds herself confronted with the emotional and material conditions that have led her family to this fractured state." --